Kinetics and mechanism of synthetic CoS oxidation process - Štrbac N.; Mihajlović I.; Živković D.; Boyanov B.; Živković Ž.; Cocić M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The results of investigation of kinetics and mechanism for synthetic a-CoS oxidation process are presented in this paper. Based on experimental data obtained using DTA and XRD analysis and constructed PSD diagrams for Co-S-O system, mechanism of synthetic a-CoS oxidation process is suggested. Characteristic kinetic parameters were obtained for experimental isothermal investigations of desulfurization degree using Sharp method.